The Local Economic Effects of Natural Resources : Evidence from Ghana - Ofori Adofo, Josephine; Tarui, Nori; Tanaka, Tomomi (World Bank, Washington, DC, 2022)
This paper estimates the welfare impacts of natural resources by analyzing Ghana’s offshore oil discovery and subsequent production. It finds substantial increases in real income, but no effect on consumption and poverty. The income effects are stronger for skilled workers. Estimates of the effects of oil discovery on employment show that employment in general increased by 4 percentage points. The positive employment effects are largely concentrated in non-oil local sectors: manufacturing and construction. The findings do not show significant impacts on employment in the agriculture and service sectors where a large proportion of individuals below the poverty line are engaged. This largely explains why the oil discovery had no effect on poverty reduction, as it benefited the non-poor rather than the poor.